2014
DOI: 10.5812/ircmj.16351
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Work Engagement Among Nurses

Abstract: Background:Engaged nurses have high levels of energy and are enthusiastic about their work which impacts quality of health care services. However, in the context of Iran, due to observed burnout, work engagement among nurses necessitates immediate exploration.Objectives:This investigation aimed to identify a suitable work engagement model in nursing profession in hospitals according to the hypothesized model and to determine antecedents and consequences related to work engagement among nurses.Patients and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
2
14
0
2
Order By: Relevance
“…Feedback is to tell the employees what they are doing continuously not waiting the annual evaluation report, aiming for improvement, progress, more motivated to perform in an acceptable manner. These results were consistent with previous studies [24,4,17,25] which concluded that job characteristics and work engagement were positively correlated to each other, beside that [21] found characteristics of job such as autonomy and feedback have motivating potential that lead to high positive outcome. Present study indicated skill variety and task identity were correlated negatively with absorption, while task significance was not correlated with work engagement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Feedback is to tell the employees what they are doing continuously not waiting the annual evaluation report, aiming for improvement, progress, more motivated to perform in an acceptable manner. These results were consistent with previous studies [24,4,17,25] which concluded that job characteristics and work engagement were positively correlated to each other, beside that [21] found characteristics of job such as autonomy and feedback have motivating potential that lead to high positive outcome. Present study indicated skill variety and task identity were correlated negatively with absorption, while task significance was not correlated with work engagement.…”
Section: Discussionsupporting
confidence: 93%
“…Vigor defined as a high level of energy and mental abilities, and the willing to put more effort in work [12], dedication refers to involvement in the work, and the employee feels the work is important, finally, absorption is the concentration, engagement and liking for the work environment. Researchers continue to investigate methods to maximize work engagement due to strong relationships between work engagement and positive outcomes and also can improve work engagement of other staff in health care organization [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work engagement is significantly related to individual and organizational factors [ 5 , 14 ]. Occupational stress is a complex biopsychosocial condition and has become a wide public concern in workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…소진(Burnout)이란 과도한 요구로 인해 심리적으로 지 치는 것과 관련된 일련의 증상을 의미하며 (Freudenberger, 1974), 소진의 상대적인 개념인 열의(engagement)는 직 무를 수행하는 과정에서 인지적, 감정적, 육체적으로 에너 지를 투입하여 완전히 몰입하는 것을 의미한다 (Kahn, 1990). 소진이 증가하고 열의가 감소하면 개인 차원에서 는 우울이 증가하고 조직차원에서는 직무에 대한 불만족 및 이직 의도의 증가한다 (Du Plooy et al, 2010;Hakanen et al, 2012). 이러한 현상은 부사관에게서도 동일하게 나타나는데, Durand(1997) et al, 1996).…”
unclassified